Synthesis, spectral characterization and biological studies of the ligand type N2O4 Schiff- bases and their (Fe (II), Zn (II), Cd (II) and Hg (II)) complexes. (Journal of the College of Basic Education, 2022)
This study aimed to synthesis and characterize hexadentate Schiff's base ligand with the general structure (H2L) containing nitrogen and oxygen donor atoms type (N2O4).The ligand (N,N)-bis-(salicylidine)-1,2-bis-(o-aminophenoxy) ethane (H2L) was prepared from the reaction of o-aminophenol with salicylaldehyde in an acidic medium and the precursor 2-(2-hydroxybenzylieneamino) phenol was obtained, this precursor was reacted with dichloroethane in alkali medium to obtain the ligand (H2L).The prepared ligand (H2L) is characterized by FT-IR,UV-Vis,1H-NMR spectra and. The ligand was reacted with some metal ions under reflux in methanol with (1:1) ratio gave complexes of the general formula [M (L)], Where: MII= Fe, Zn , Cd and Hg. These complexes were characterized by atomic absorption, chloride content, I.R, U.V-Vis spectra, molar conductivity, HPLC, melting point, and biological activity were tested for some complexes of this ligand .The molar conductance showed that, all complexes are non-electrolyte. According to all these measurements . The proposed structures for (H2L) complexes were an tetrahedral geometry for FeII , Zn II , CdII and HgII . Keywords: Schiff-base ligand; (N,N)-bis-(salicylidine)-1,2-bis-(o-aminophenoxy) ethane; structural and biological studies